1989
DOI: 10.1063/1.457356
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of methanol and ethanol activated by a chemical reaction or by light

Abstract: When energized sufficiently either vibrationally or electronically, ROH (where R is methyl or ethyl) can dissociate to form H atoms and RO radicals. We have determined the translational energy release (〈ETr 〉=0.82Eavl ) and angular distribution (β=−0.60±0.03) from the laser induced fluorescence spectra of H atoms produced in the 193 nm photodissociation of CD3OH. We have also determined that the quantum yield for producing H from CD3OH is 0.86±0.10. In contrast, the reaction of O(1D)+CH4 which produces vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
86
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 33 publications
20
86
1
Order By: Relevance
“…A photodissociation quantum yield of CH 3 O of 0.86 ± 0.10 has been found at 193.3 nm (Satyapal et al, 1989) in qualitative agreement with analysis of the end-products of the methanol photodissociation at 184.9 nm (Porter and Noyes, 1959;Buenker et al, 1984 Details on the HIRAC-based FAGE instrument for the detection of OH and HO 2 has been presented previously (Winiberg et al, 2015). Figure 1 shows a schematic cross section of the instrument inlet and the two fluorescence detection cells.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…A photodissociation quantum yield of CH 3 O of 0.86 ± 0.10 has been found at 193.3 nm (Satyapal et al, 1989) in qualitative agreement with analysis of the end-products of the methanol photodissociation at 184.9 nm (Porter and Noyes, 1959;Buenker et al, 1984 Details on the HIRAC-based FAGE instrument for the detection of OH and HO 2 has been presented previously (Winiberg et al, 2015). Figure 1 shows a schematic cross section of the instrument inlet and the two fluorescence detection cells.…”
Section: Introductionmentioning
confidence: 69%
“…Although it is known, based on end-product analysis, that the scission of the O-H bond is a major photolysis channel of methanol at 184.9 nm (Buenker et al, 1984;Porter and Noyes, 1959), the photodissociation quantum yield of CH 3 O at 184.9 nm, CH 3 O, 184.9 nm , has not yet been reported. Here it is assumed that CH 3 O,184.9 nm is equal to the photodissociation quantum yield at 193.3 nm, CH 3 O, 193.3 nm = 0.86 ± 0.10, which has been reported (Satyapal et al, 1989 …”
Section: Calibration For Methoxy Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In photolysis of methanol at 193 nm, however, the dominant process is O-H bond rupture via the S 1 state. 14 In the photolysis of CD 3 OH at 193 nm, the ratio of H : D was determined to be 0.86 : 0.14; 82% of the total available energy was deposited into the translational degrees of freedom. Wen et al 15 detected H and D atoms from the photodissociation of three isotopic variants of methanol using the high-n Rydberg atom time-of-flight (HRTOF) technique.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the yield of H 2 was less than 25% of the yield of H from (b). Satyapal et al [1147] observed the production of H atoms in a pulsed laser experiment and reported a yield of H of (25±8)%. Matsumi et al [886] measured the yields of H and O( 3 P) in low pressure gas mixtures and reported that the yield of H was (15±3)% and the yield of O( 3 P) was <5%.…”
Section: Notes Tomentioning
confidence: 99%